2006
DOI: 10.5507/bp.2006.056
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism in active Crohn's disease: Pre-results

Abstract: Background:Crohn's disease (CD) is a chronic relapsing disease. Especially acute period may be associated with metabolic disturbances. Alteration of lipid metabolism has been described in critically ill patients and hypocholesterolemia is associated with poor prognosis. The human organism acquires cholesterol by two principal processes -synthesis de novo, and absorption from the diet. It is possible to assess, using cholesterol synthesis markers (lathosterol) and cholesterol absorption markers (sitosterol, cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…These findings agree well with the recent literature of multiple GWA studies [7, 36, 37]. Substantial alternation of lipid metabolism has been shown in patients with acute CD associated with metabolic disturbances [38]. In addition, our SCPCA found a set of statistically significant pathways related with regulation of protein kinase activity.…”
Section: Resultssupporting
confidence: 92%
“…These findings agree well with the recent literature of multiple GWA studies [7, 36, 37]. Substantial alternation of lipid metabolism has been shown in patients with acute CD associated with metabolic disturbances [38]. In addition, our SCPCA found a set of statistically significant pathways related with regulation of protein kinase activity.…”
Section: Resultssupporting
confidence: 92%
“…3 A). Previous observational studies have reported a distinct lipid profile in CD patients compared with healthy population [ 88 , 89 ]. And growing evidence showed emulsifying omiga-3 fatty acids maybe a potential supplementary in maintaining remission of CD patients [ 90 , 91 ].…”
Section: Heterogeneity Of Various Tissue Types Selected In Eqtlmentioning
confidence: 99%